Utilización de estrategias y dinámicas grupales para el proceso de enseñanza aprendizaje en el area de estudios sociales de los estudiantes del décimo año de educación básica de la unidad educativa Dr Alfredo Pérez Guerrero del cantón Santa Rosa periodo lectivo 2012-2013 - Cruz Sánchez, Henry Darwin (2013)
It is necessary to overcome the traditional methods that have led the student to domestication and alignment, becoming taxable and repetitive, with rudimentary skills that only serve to keep you tied to the yoke of oppression and conformism.